The first complete mitochondrial genome of Rohanella titteya (Cypriniformes: Cyprinidae) and its phylogenetic analysis - Yu-Hui Tao; Jin-Qiang Cheng; Jin-Yang Li; Cheng-Pu Lu; Jie Chen; Wei Liu (Mitochondrial DNA. Part B. Resources)
We report the first complete mitochondrial genome of Rohanella titteya (Deraniyagala 1929), revealing a 16,715 bp genome containing 37 genes (13 protein-coding genes, 22 tRNA genes, 2 rRNA genes). Phylogenetic analysis based on mitochondrial genomic data of R. titteya and 11 Cyprinidae species showed that it clustered most closely with the mitogenome of Puntius eugrammus, offering no support for the recent transfer of this species to the new genus Rohanella. The mitogenome presented here provides a useful resource for both conservation and future Cyprinidae taxonomy.